2014
DOI: 10.1163/15730255-12341270
|View full text |Cite
|
Sign up to set email alerts
|

Mushārakah—A Realistic Approach to the Concept in Islamic Finance and its Application to the Agricultural Sector in Pakistan

Abstract: Food is one of the basic necessities that is imperative for human survival. The majority of farmers related to agriculture belong to the lower class and are hence not in a position to fulfil their agricultural needs. Therefore, they must borrow from various sources, e.g., from individuals, organizations, and/or banks, using interest-based lending, which Muslims are prohibited from doing according to the Sharīʿah. Here the concept of mushārakah (participatory mode of finance) is the best option. The present wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In contrast, it is rare to find some reference of this financing approach from Islamic perspective. Most of the studies are investigate the Islamic microfinance practice in agriculture (Obaidullah, 2015) or appropriate modes of finance in some specific case and area (Moh'd et al, 2017;Oladokun et al, 2015;Saqib et al, 2014) although agricultural value chain finance is quite mainstream in agriculture and development sectors. Obaidullah (2015) undertakes a review of various Islamic microfinance interventions in agriculture where it is strongly argued how the conventional products and services are not acceptable in the Islamic societies.…”
Section: Previous Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, it is rare to find some reference of this financing approach from Islamic perspective. Most of the studies are investigate the Islamic microfinance practice in agriculture (Obaidullah, 2015) or appropriate modes of finance in some specific case and area (Moh'd et al, 2017;Oladokun et al, 2015;Saqib et al, 2014) although agricultural value chain finance is quite mainstream in agriculture and development sectors. Obaidullah (2015) undertakes a review of various Islamic microfinance interventions in agriculture where it is strongly argued how the conventional products and services are not acceptable in the Islamic societies.…”
Section: Previous Studiesmentioning
confidence: 99%
“…It is also found that, there is no one-size-fits-all mode of finance in agriculture sector. For instance, Saqib et al (2014) suggest types of musharaka with the concepts of muzara'a and musaqa to finance agriculture in Pakistan particularly in urban areas as compared to rural areas but still push Islamic banks to work for prosperity of the poor. Oladokun et al (2015) develop a Muzara'a supply chain model although it is similar with value-chain finance concepts through land partnership.…”
Section: Previous Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Value chain developed according to the Islamic approach, which could bring a solution for financing agriculture, has encountered problems during its practice in Islamic banks (Saqib et al, 2014;Hussain & Syed Ja'afar Alhabshi, 2016). As mentioned by Webber and Labaste (2010), value chain focuses on value creation-typically via innovative products or processes as well as marketing-and also, on the allocation of incremental value.…”
Section: Introductionmentioning
confidence: 99%